A one-pot synthesis of N2,6-diaryl-5,6-dihydro-1,3,5-triazine-2,4-diamines and systematic evaluation of their ability to host ethanol in crystals - Ahmad Junaid,; Tan, Yee Seng *; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Royal Society of Chemistry, 2019)
A convenient one-pot method for the preparation of N2 ,6-diaryl-5,6-dihydro-1,3,5-triazine-2,4-diamines was developed using a three-component synthesis of 1,6-diaryl-1,6-dihydro-1,3,5-triazine-2,4-diamines followed by their Dimroth rearrangement to the desired products. The prepared compounds crystallized from ethanol as ethanol clathrates (1 : 1). X-ray crystallography on several products confirmed the adoption of 5,6-dihydro-tautomer. The thermal analysis and powder X-ray diffraction experiments on selected compounds suggested that thermal desolvation of crystals was irreversible.